'We are not the shoes of white supremacists': a critical race perspective of consumer responses to brand attempts at countering racist associations. Issue 13 (1st September 2020) - Wei, ML; Bunjun, Benita
ABSTRACT: Recently, brands have come under fire for being associated with groups like neo-Nazis and white nationalists. In reaction, brands have tried to distance themselves through appeals to diversity. This research contributes to the literature on multiculturalism in marketing through a critical race perspective of how and why consumers participate in social networks in efforts to counter racism. Our findings identify three ways in which consumers respond, by punishing, advising, and defending, and highlight the relevance of circulating affect and exalted national subjects for understanding the practice and impact of multiculturalism in marketing on social media. This research contributes to our understanding of multiculturalism in marketing by extending ideas of impact beyond questions of personal cognitive change. By connecting issues of race to the larger project of nation-building, this research also complements psychological accounts of how consumers engage with brands in social networks as they work to take up diversity.